The Effect of Strategic Orientation and Marketing Capabilities on Business Performance: A Capacity Mediation Approach - Abdul Halim; Siti Asiyah; Dwiyani Sudaryanti (Universitas KH. Abdul Chalim Mojokerto, 2026)
Business performance is an important indicator in assessing the success and sustainability of companies amid increasingly dynamic business competition. Market orientation, entrepreneurial orientation, and marketing capabilities are seen as strategic resources that have the potential to improve business performance, but previous empirical findings still show mixed results. These differences indicate the need for explanatory mechanisms, one of which is through absorptive capacity. This study focuses on how market orientation, entrepreneurial orientation, and marketing capabilities affect business performance, as well as the role of absorptive capacity in mediating this relationship. This study aims to analyze the direct effects of market orientation, entrepreneurial orientation, and marketing capabilities on business performance, as well as to examine the mediating role of absorptive capacity. The research method used is a quantitative approach with a survey design. Primary data were collected through questionnaires administered to business actors and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results show that market orientation, entrepreneurial orientation, and marketing capabilities have a positive and significant effect on business performance. In addition, absorptive capacity has a positive effect on business performance and is proven to play a significant mediating role in the relationship between market orientation, entrepreneurial orientation, and marketing capabilities on business performance. These findings confirm that strengthening absorptive capacity as a company's dynamic ability to absorb and utilize external knowledge is key to improving business performance in a sustainable manner